Fires of winter - Lindsey, Johanna; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1980)
When the Vikings kidnap her, Lady Brenna vows she will never be a slave, but is, nonetheless, attracted to Garrick, the Norseman destined to be her master.
Keywords: Vikings